Tax me if you can: An artefactual field experiment on dishonesty - Catrine Jacobsen; Marco Piovesan (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2015)
In this paper, we test whether increased salience of a tax charge increases dishonesty using a version of the die-under-cup paradigm. Participants earn money in proportion to the outcome reported and, thus, have an incentive to over-report. We find a significant increase in high outcomes in the presence of a tax frame suggesting that participants use the tax as an excuse to rationalize their dishonest act. In addition, we tested whether adding an explanation for the adoption of the tax would increase honesty. We find evidence for reversed dishonesty with participants reporting significantly more low outcomes. These results warn policy makers about the non-trivial relationship between taxation charges and dishonesty.
Keywords: C9; D03; H26; 330; Dishonesty; Tax evasion; Deduction; Framing